Pengaruh Brand Experience Terhadap Brand Satisfaction, Brand Trust dan Brand Loyalty (Studi Pada Konsumen Make-Up Brand Impor di Surabaya) - Pertiwi, Agata Rahmi; Djawahir, Achmad Helmy; Andarwati, Andarwati (Jurnal Manajemen dan Kewirausahaan, 2017)
The purposes of this study is to describe and analyze the direct and indirect effect of brand experience on brand satisfaction, brand trust, and brand loyalty of consumers make-up brand cosmetics imports in Surabaya. This study uses questionnaires as the research instrument with 100 respondents as the sample. Sampling technique is convenience sampling. This study uses Partial Least Square (PLS)s to analyzed the data. The results shows that there is a significant direct effect on the brand experience on brand satisfaction, brand trust, and brand loyalty. The results also shows that there are significant indirect influence between brand experience on brand loyalty through brand trust and brand experience on brand trust through brand satisfaction. The other result shows that there is no significant relationship between brand satisfaction on brand loyalty and brand experience on brand loyalty through brand satisfaction.Â https://doi.org/10.26905/jmdk.v5i2.1355 Â